Simplified Roux-en-Y reconstruction after laparoscopic radical distal gastrectomy for gastric cancer - Qian, Yawei; Zhou, Guang; Chang, Feifei; Ping, Xiaochun; Wang, Guoliang (Frontiers in Surgery, 2022)
Background: Although there were a variety of strategies for the alimentary tract reconstruction of patients with gastric cancer underwent laparoscopic radical distal gastrectomy, it remains controversial regarding which procedure is optimal. We developed a simple technique for Roux-en-Y reconstruction during laparoscopic surgery, and evaluated its technical feasibility and safety. Methods: Seventy-one cases of modified Roux-en-Y reconstructions after laparoscopic radical distal gastrectomy were consecutively performed in our hospital, from November 2020 to March 2022. A retrospective review of medical data was conducted. Intraoperative and postoperative outcomes, including operation time and incidence of postoperative complications, were collected and analyzed. Results: All procedures of laparoscopic distal gastrectomy with D2 lymph node dissection were successfully completed without any intraoperative complication. The mean number of retrieved lymph node was 38.8 ± 10.6. Mean operative time was 223.5 ± 42.4 minutes, whereas intraoperative blood loss was 102.2 ± 96.3 ml. None postoperative mortality was recorded. Six patient (8.5%) experienced postoperative complications and were managed conservatively. In addition, only two patients (2.8%) required re-hospitalization during a median short-term follow-up period of 6 months. Conclusions: The modified method is a simple and safe approach for laparoscopic radical distal gastrectomy.